APPLICATION OF LASER-INDUCED BREAKDOWN CAVITATION BUBBLES FOR CELL LYSIS IN VITRO - JASIKOVA, DARINA; RYSOVA, MIROSLAVA; KOTEK, MICHAL (International Journal of Applied Pharmaceutics, 2019)
Objective: Understanding the basic mechanism of the cavitation bubble action on living cells as a crucial step of development and application of sophisticated methods based on controlled cavitation in cell behaviour manipulation. Optimisation of parameters in order to expand cell lysis region created by a single bubble. Methods: The cavitation bubbles are generated by the laser-induced breakdown method. The impact of controlled cavitation bubble on the biological system is synchronously monitored under a microscope and recorded. Visualization of the cavitation bubble course is monitored by a highspeed camera. The impact of technology on the healthy confluent cell layer is verified. Evaluation of the cavitation bubbles´ effect on cells in real time and by subsequent analysis of the cell lysis region and impact of the cavitation bubble on cell viability is carried out by optical visualization and life/ dead fluorescence staining. Results: Cavitation bubble induced in distance of 1.5 mm from the cell surface overcomes properties of sessile bubble and enables to create cell lysis region over 1000 μm in diameter due to transient shear stress produced by liquid displaced by the bubble expansion. Conclusion: Cell lysis region is strongly dependent on the spot laser energy (SLE) and the bubble induction distance from cells. This knowledge is crucial for application in chemical free cell lysis in vitro, wound induction for experimental purposes and cell layers patterning in desired scale.